Consumers' willingness to pay for environmentally certified timber products: a comparison between 2003 and 2012 - Mohamed, Shukri; Yaakob, Sam Shor Nahar; Abdullah, Rahim; Mohd Selamin, Masfitriniza (Forestry Department Peninsular Malaysia, 2013)
Consumers' willingness to pay (WTP) price premiums for environmentally certified timber products (ECTPs) is a major contentious issue in producing and marketing of such timber product. This paper compares findings of two surveys conducted in 2003 and 2012 that examined WTP, a price premium for an ECTP among consumers in Malaysia. The purpose was to determine if there were changes in consumers' WTP after almost a decade when forest management and timber product certification was first introduced in the country. A similar base price for the timber product made of non-certified timbers was presented to the respondents in both surveys. The percentage of respondents who indicated a WTP a price premium has increased from 38% in 2003 to 70.5% in 2012. The average price premium the respondents would be willing to pay has slightly increased from 14.4% to16.5% in 2003 and 2012, respectively. The findings seem to show an increasing consumer support and WTP for ECTPs in Malaysia.